Workload control under continuous order release - Fernandes, Nuno Octávio Garcia (2011)
Past research on workload control (WLC) has been essentially focused on discrete order release. This means that release of orders to the shop floor takes places on a periodic basis. Continuous order release has been somehow neglected, in spite of its apparent potential for improving system performance, including the reduction of order flow times. This paper addresses a simulation study of this order release approach. The study contributes for improving the basis for setting workload norms and selecting the workload control strategy under continuous order release. Additionally, it gives insights on the choice of routing alternatives, which facilitate the linkage of continuous order release mechanisms with the specific characteristics of the shop floor.